Complexities of Cross-Cultural Interaction in Jasmine and the Tiger's Daughter: Exploring the Cross-Cultural Dilemma in Bharati Mukherjee's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2022)
A substantial portion of a person's beliefs, morals, behaviours, and attitudes are shaped by thesociety in which they were brought up during their formative years. These qualities have an effect on theway a person thinks, as well as the way that person approaches the world around him in general. Ancontact between cultures takes happen when one individual is presented with the values and beliefs ofanother society .Assimilation into American culture creates tension in many of the immigrant protagonists,which in turn leads to tension, an offshoot, resulting from Cultural Interaction. In its discussion of thenovels chosen for this study, this chapter makes an analysis of the characters who come across Cross-Cultural Conflict. Bharati Mukherjee, much like a large number of other post-modern writers, has focusedon the challenges and difficulties experienced by Indian immigrants living in the United States orelsewhere in the Western world. The ladies in her books go through a cross-cultural dilemma that isportrayed vividly in her writing. She, herself, as an immigrant, had a tough time adapting to the culture,customs, and traditions of the country, and this is what she portrays via the cultural crisis experiencedby her female heroine